2021
DOI: 10.1038/s41598-021-02274-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low muscle mass and associated factors in community-dwelling older adults in Singapore

Abstract: The population is rapidly aging worldwide, and there is an age-related decline in muscle mass. Therefore, it is important to examine the prevalence and associated factors of low appendicular skeletal muscle mass index (ASMI) in older adults. The objectives of this cross-sectional study were (i) to determine the prevalence of low ASMI (ASM/height2) and (ii) to identify factors associated with low ASMI. This study included 1211 community-dwelling adults aged ≥ 65 years. Low ASMI was defined as < 7.0 kg/m2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…In addition to the significant increase in risk of sarcopenia in malnourished versus normal nutrition in older adults, with odds ratio ranging from 9.9 to 13.6 [ 11 , 29 ], our findings show that there is a doubling of odds ratio for sarcopenia amongst those at high risk versus medium risk of malnutrition. This association is further highlighted in a recent study from our group, which reported that compared to older adults with normal nutritional status, the odds of having low ASMI was 3.58 for those at medium risk of malnutrition and 12.50 for those at high risk of malnutrition [ 45 ]. Taken together, the presence of malnutrition is a strong predictor of concomitant poor muscle health.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition to the significant increase in risk of sarcopenia in malnourished versus normal nutrition in older adults, with odds ratio ranging from 9.9 to 13.6 [ 11 , 29 ], our findings show that there is a doubling of odds ratio for sarcopenia amongst those at high risk versus medium risk of malnutrition. This association is further highlighted in a recent study from our group, which reported that compared to older adults with normal nutritional status, the odds of having low ASMI was 3.58 for those at medium risk of malnutrition and 12.50 for those at high risk of malnutrition [ 45 ]. Taken together, the presence of malnutrition is a strong predictor of concomitant poor muscle health.…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, using the individual criteria of the AWGS updated consensus 2019 [2], 81% of participants had low ASMI, 83% had low muscle strength, and 78% had low physical performance. Across Asia, low muscle mass was reported to occur commonly in community-dwelling older adults, ranging from 20 to 65% [12,[44][45][46][47]. Specifically referring to sarcopenia in older community-living Asian adults, the prevalence ranged from 18 to 46% [3,[8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People in the older population, including those living in the community, are among the most vulnerable to malnutrition. Poor nutrition in older people commonly leads to declining physical function, along with social and economic burdens (58,(83)(84)(85)(86)(87)(88). However, these problems have often gone unrecognized until very recently.…”
Section: What Does the Recent Evidence Show About Nutritional Interve...mentioning
confidence: 99%
“…From the age of 45, the skeletal muscle mass is progressively lost (2). The loss of skeletal muscle is associated with malnutrition, sarcopenia, loss of functionality and other adverse effects in older adults (3)(4)(5)(6)(7). Therefore, it should be a priority to assess this body composition component in this age group.…”
Section: Introductionmentioning
confidence: 99%